The impacts of the interaction of genetic variation, CYP11β2 and NEDD4L, with sodium intake on pediatric obesity with gender difference: a 3-year panel study - Lee, M; Kwon, D Y; Park, J (International Journal of Obesity, 2017)
Backgrounds/Objectives: This panel study was to predict the incidences of pediatric obesity by the interaction of sodium (Na) intake and nine single-nucleotide polymorphisms (SNPs) of salt-sensitive genes (SSGs), ACE (angiotensin-converting enzyme), ADD1 G460W , AGT M235T , CYP11β2 (cytochrome P 450 family 11-subfamily β-2, -aldosterone synthase), GNB3 C285T , GRK4(A142V) (G-protein-coupled receptor kinases type 4), GRK4 ( A486V ), NEDD4L (neural precursor cell expressed developmentally downregulated 4 like; rs2288774) and SLC12A3 (solute carrier family 12 (Na/Cl transporters)-member 3), selected from genome-wide association study. Subjects/Methods: Non-obese (non-OB) Korean children of 9 years old were recruited from eight elementary schools in Seoul in 2007 and 2009, each. Follow-up subjects (total=798) in 2010 and 2012 were final participants. Participants were classified as OB group for those whose body mass index were over the 85th percentile using the ‘Korean National Growth Charts’, and others were classified as non-OB. With nine SNPs typing, the genetic interaction with the variation of Na intake for 3 years was evaluated as an obesity risk. Results: The obesity incidence rate for non-OB children at baseline after 3 years was 10.31%. Na intake in non-OB after 3 years was significantly decreased compared with the baseline, whereas Na intake reduction was undetectable in OB. We found gender differences on association between the changes of Na intake and the obesity incidence for 3 years by the SSG variation. Odds ratio for the obesity risk was 5.75 times higher in girls having hetero/mutant types of NEDD4L with higher Na intakes (Q2+Q3+Q4 in quartiles) compared with that in the wild type with the lowest Na intake (Q1). Girls with hetero/mutant of CYP11β2 tended to increase the obesity incidence as Na intake increased (Q1<Q2<Q3<Q4, P -value trend=0.047). The other seven SNPs of SSGs had no significance over Na intake. Conclusions: From this panel study and the previous cross-sectional study, we found CYP11β2 as the common gene, powerful to explain the interaction between obesity incidence and Na intake, in particular, among girls. Girls with hetero/mutant allele of this gene should reduce their daily Na intake to prevent obesity.